(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Lehun V. Сompetence approach during professional formation of future expert. The article discusses the features of the competency approach to learning that affect the formation of socially significant qualities of future professional and make it possible to provide a sufficient level of his professional development